Aplikasi Pengelolaan Pendapatan dan Pengeluaran Kas Pada Rafa Laundry Berbasis Web - Yeni Mardi; Andi Saputra; Sri Murni; Weiskhy Steven Dharmawan (Jurnal Sistem Informasi Akuntansi, 2020)
Rafa Laundry is a service business that offers cleaning clothes, carpets, dolls, bags and other textile materials. In every business process, Rafa Laundry still uses paper media in the form of books and notes, this is because Rafa Laundry has not implemented a computerized system. As a result of the computerized running system, the recording process is vulnerable to loss and damage, another weakness, namely processing data into information or reports that take a long time. This computerized system makes Rafa Laundry employees have to summarize daily transactions, income transactions and disbursement transactions, income transactions paid by customers are income for Rafa Laundry. Therefore, in this study to design and build a management application of income and cash outlays at Rafa Laundry, by applying the waterfall software development method.